Reference intervals for plasma, urinary, and salivary concentrations of free metanephrines in dogs: Relevance to the diagnosis of pheochromocytoma - Marit F. van denBerg; Hans S. Kooistra; Guy C. M. Grinwis; Sebastiaan A. vanNimwegen; Martijn vanFaassen; Ido P. Kema; Erik Teske; Sara Galac (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Measurement of free metanephrines is recommended for screening of pheochromocytoma (PCC) but requires appropriate reference intervals (RIs). Hypothesis/Objectives To report RIs for plasma, urinary and salivary concentrations of free metanephrines and to determine the diagnostic performance of plasma free normetanephrine (pNMN) and metanephrine (pMN) concentrations in dogs with PCC, hypercortisolism (HC), and nonadrenal illness (NAI). Animals Eighty healthy dogs, 11 PCC dogs, 25 HC dogs, 6 NAI dogs. Methods Plasma, urine, and saliva were collected prospectively from healthy dogs, and free metanephrine concentrations were determined by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). In addition, medical records of dogs that had plasma free metanephrine concentrations measured by LC‐MS/MS between 2018‐2021 were studied retrospectively. Results The RIs for free metanephrines in plasma, urine and saliva are reported. Dogs with PCC had significantly higher pNMN than dogs with HC (P < .001) and NAI (P = .002). The PCC dogs had significantly higher pMN than HC dogs (P < .001), but not higher than NAI dogs (P = .29). Using the upper reference limit, pNMN (>3.56 nmol/L) showed high sensitivity (100%, 95% confidence interval [CI]: 72‐100) and specificity (94%, 95% CI: 79‐99) for diagnosis of PCC, whereas pMN (>2.49 nmol/L) showed moderate sensitivity (73%, 95% CI: 39‐94) and high specificity (94%, 95% CI: 79‐99). Conclusions and Clinical Importance With establishment of these RIs, biochemical testing for PCC in dogs can be substantially improved. Measurement of pNMN is superior to pMN in dogs with PCC.